Pengaruh Diversitas Gender Terhadap Pengungkapan Sustainability Development Goals - Dessy Noor Farida (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2019)
Public awareness of the environment will be increasingly damaged due to industrial activities of large companies, making the community need information about the extent to which the company is responsible for the damage. This ecological crisis is driving concern from various countries in the world by formulating a Sustainability Development Goals that are expected to improve the quality of human life. Representation of women in the leadership of a company can be one of the drivers of companies to be more concerned with voluntary disclosures. This research is a quantitative research that uses multiple linear regression with a sample of companies listed on the ISSI for 4 consecutive years. The results showed that the presence of women on the board of directors did not affect the disclosure of SDGs. Whereas the presence of women in the board of commissioners has a significant effect on the disclosure of SDGs. The influential control variables are only the size of the company, while the variables of profitability and leverage have no effect.Keywords: Sustainability Development Goals (SDGs), Board of Directors, Board of Commissioners, Gender Diversity